Analisis Faktor-Faktor Pemilihan Lokapasar Favorit Di Kalangan Mahasiswa ITS - Jason Ho; Alfa Renaldo Aluska; Aulisa Rizki Amanda; Nur Aini Rakhmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the midst of internet advancement, the presence of marketplaces brings many positive impacts. Local marketplace users are predominantly coming from Generation Z, and the majority of ITS students, as observed during this research, is part of the group. The purpose of this study is to identify the most favorite marketplace and the factors influencing the preference of these favorite marketplaces among ITS students. The preference factors are based on 13 factors that affect shopping behavior. The method employed is a survey-descriptive using 55 respondents in answering the questionnaire. The research results indicate that advertising and communication, certification and security, and warranty are the three factors with the highest urgency in choosing a favorite local market. Additionally, discount, website, and review and complain are the three factors with the lowest urgency. This study reveals that consumers or users prioritize the value offered by marketplaces over factors such as price and discounts.